High-performance FeSiAl magnetic powder core, preparation method and application thereof
By using the FeSiAl magnetic powder core preparation method, small-particle-size iron-based amorphous soft magnetic powder is mixed with FeSiAl soft magnetic powder and formed with low-melting-point pure Al powder to form a nanocrystalline structure and an alumina insulating coating layer. This method solves the problems of high loss and poor bonding force of existing magnetic powder cores at high frequencies, and realizes a high-frequency, low-loss and high-strength magnetic powder core.
Patent Information
- Application Number
- CN202511961405.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-12-24
AI Technical Summary
Existing ferroalloy magnetic powder cores suffer from high losses at high frequencies, while amorphous and nanocrystalline magnetic powder cores are brittle and have poor bonding strength, making it difficult for the strength and performance of magnetic powder cores to meet the requirements of high frequency and miniaturization.
The FeSiAl magnetic powder core preparation method is adopted, which combines gas atomization powder preparation with the mixing of small-particle-size iron-based amorphous soft magnetic powder and FeSiAl soft magnetic powder, and hot pressing sintering under the bonding effect of low-melting-point pure Al powder to form a nanocrystalline structure and an alumina insulating coating layer, thereby improving the bonding force and insulation effect.
It significantly improves the high-frequency magnetic properties and strength of the magnetic powder core, reduces high-frequency loss, and meets the needs of high-frequency and miniaturized electronic products.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of soft magnetic materials technology, specifically relating to a high-performance FeSiAl magnetic powder core, its preparation method, and its application. Background Technology
[0002] Magnetic powder cores are soft magnetic composite materials manufactured using powder metallurgy. They possess excellent comprehensive properties and are widely used in various electronic components such as communications, energy, automotive, filters, and instrument transformers. With the development of electronic products towards miniaturization, high frequency, energy efficiency, and high sensitivity, magnetic powder cores are required to possess high strength, high permeability, high magnetic property stability, high saturation magnetic induction, and low loss.
[0003] Magnetic powder cores can be classified into three main categories based on their material composition: ferroalloy magnetic powder cores, ferrite magnetic powder cores, and amorphous nanocrystalline magnetic powder cores. Ferroalloy magnetic powder cores have low resistivity but high eddy current losses at high frequencies, limiting their application to low to mid-frequency ranges up to 100kHz. Therefore, surface insulation treatment of the ferroalloy magnetic powder particles is an effective way to reduce these losses. Even so, conventional ferroalloy magnetic powder cores still cannot operate at higher frequencies. Amorphous nanocrystalline magnetic powder cores possess higher permeability and lower AC losses, enabling them to withstand higher magnetic field strengths and frequencies. Therefore, composite modification of ferroalloy magnetic powder cores with amorphous nanocrystalline magnetic powder is an effective means to improve the overall performance of magnetic powder cores and reduce costs. However, amorphous nanocrystalline magnetic powder is relatively brittle, and the stress difference between it and ferroalloy magnetic powder is significant, resulting in poor bonding strength. This often leads to hybrid magnetic cores failing to meet required strength and performance. Summary of the Invention
[0004] In view of the shortcomings and deficiencies of the existing technology, the primary objective of this invention is to provide a method for preparing high-performance FeSiAl magnetic powder cores.
[0005] Another objective of this invention is to provide a high-performance FeSiAl magnetic powder core prepared by the above method.
[0006] Another object of the present invention is to provide the application of the above-mentioned high-performance FeSiAl magnetic powder core in the fields of AI computing chips, servers and communication equipment.
[0007] The objective of this invention is achieved through the following technical solution:
[0008] A method for preparing a high-performance FeSiAl magnetic powder core includes the following preparation steps:
[0009] (1) The composition system is Fe (100-x-y-z) Si x B y M zIron-based amorphous materials are pulverized by gas atomization to obtain iron-based amorphous soft magnetic powder; wherein 3≤x≤20, 2≤y≤15, 1≤z≤5, and M is at least one metallic element selected from Cu, Nb, V, Ti, and Cr;
[0010] (2) Mix iron-based amorphous soft magnetic powder with FeSiAl soft magnetic powder, pure Al powder, aluminate coupling agent, lubricant and organic binder evenly to obtain a mixed slurry;
[0011] (3) The obtained mixed slurry is first hot-pressed and cured under vacuum conditions at a temperature of 60~100℃, and then hot-pressed and annealed under oxygen atmosphere conditions at a temperature of 750~1000℃ to obtain high-performance FeSiAl magnetic powder core.
[0012] Furthermore, the average (D50) particle size of the iron-based amorphous soft magnetic powder in step (1) is 0.2~10μm.
[0013] Furthermore, the average particle size of the FeSiAl soft magnetic powder in step (2) is 5~50μm.
[0014] By using small-particle-size iron-based amorphous soft magnetic powder, the gaps between FeSiAl soft magnetic powders can be filled better, and the bonding effect of low-melting-point pure Al powder can achieve a good combination between iron-based amorphous soft magnetic powder and FeSiAl soft magnetic powder, thereby improving the strength and performance of the magnetic core.
[0015] Furthermore, the average particle size of the pure Al powder in step (2) is 0.2~5μm.
[0016] Further, the lubricant mentioned in step (2) is zinc stearate, magnesium stearate or polyvinyl ether.
[0017] Further, the organic binder mentioned in step (2) uses a thermosetting epoxy resin, acrylic resin or organosilicon resin with a solid content of 20-40% and a diluent of ethyl acetate, cyclohexanone, propylene glycol methyl ether acetate, toluene or xylene.
[0018] Furthermore, the mass fraction of each material in step (2) is as follows:
[0019] 0.5-10 parts of iron-based amorphous soft magnetic powder, 100-120 parts of FeSiAl soft magnetic powder, 0.5-5 parts of pure Al powder, 0.2-1 parts of aluminate coupling agent, 0.2-1 parts of lubricant, and 1-10 parts of organic binder.
[0020] In the above material composition, the iron-based amorphous soft magnetic powder is mainly used to fill the gaps between the FeSiAl soft magnetic powder and form a nanocrystalline structure during the subsequent high-temperature hot-pressing annealing sintering process, thereby improving high-frequency loss performance. Pure Al powder has a low melting point, which, on the one hand, can act as a binder phase during the subsequent high-temperature hot-pressing annealing sintering process to fill the air gaps generated by the thermal-oxidative decomposition of the organic phase, thereby improving the bonding force between the iron-based amorphous soft magnetic powder and the FeSiAl soft magnetic powder and the core strength; on the other hand, it can oxidize in situ at the air gaps generated by the thermal-oxidative decomposition of the organic phase to form an alumina insulating coating layer, further improving the high-frequency loss performance of the magnetic powder core. Aluminate coupling agents and lubricants are used to improve the mixing and dispersion effect of the soft magnetic powder and the organic binder. The organic binder is used for bonding the soft magnetic powder and forming an initial uniform organic coating layer on the surface of the soft magnetic powder.
[0021] Furthermore, the pressure for hot pressing and curing in step (3) is 100~300MPa, and the time is 2~6h.
[0022] Pre-vacuum hot-press curing can reduce the oxygen content in the matrix and avoid excessive oxidation inside the FeSiAl soft magnetic powder. This allows the oxidation reaction during the subsequent hot-press annealing and sintering process to occur directionally at the air gaps generated by the thermal oxygen decomposition of the organic coating layer, thereby achieving a uniform and good insulation coating effect.
[0023] Furthermore, the oxygen-containing atmosphere mentioned in step (3) is an air atmosphere or a mixed atmosphere of oxygen and argon.
[0024] Furthermore, the pressure of the hot pressing sintering treatment in step (3) is 500~800MPa, and the time is 10~90min.
[0025] The hot-pressing sintering process in a high-temperature oxygen-containing atmosphere promotes the crystallization process of iron-based amorphous soft magnetic powder and improves its magnetic properties. On the other hand, it causes the organic components to decompose in a hot oxygen atmosphere and melts the pure Al powder to fill the air gaps. Furthermore, it oxidizes in situ to generate an alumina insulating coating layer, thereby improving the core strength and high-frequency magnetic properties.
[0026] A high-performance FeSiAl magnetic powder core was prepared by the above method.
[0027] The above-mentioned high-performance FeSiAl magnetic powder cores are used in AI computing chips, servers, and communication equipment.
[0028] Compared with the prior art, the beneficial effects of the present invention are:
[0029] (1) The magnetic powder core of the present invention uses high-frequency, low-loss and high-permeability iron-based amorphous nanocrystalline soft magnetic powder to modify the FeSiAl magnetic powder core, which can significantly improve the high-frequency magnetic properties of the magnetic powder core. In addition, low-melting-point pure Al powder is used as the binder phase and its in-situ oxide is used as the insulating coating phase, which can significantly improve the bonding force between soft magnetic powders and the insulating coating effect.
[0030] (2) The method for preparing the magnetic powder core of the present invention uses high-temperature thermal oxygen decomposition of organic binder and in-situ filling and directional oxidation of low-melting-point pure Al powder to achieve insulating coating of soft magnetic powder. This solves the technical problems of conventional organic insulating layer coating being unable to be sintered at high temperature, resulting in low magnetic powder core strength and poor bonding force of inorganic insulating layer coating, requiring ultra-high pressure (>1GPa) to improve the magnetic powder core strength, which easily leads to insulation layer damage and reduced insulation coating effect. Detailed Implementation
[0031] The present invention will be further described in detail below with reference to embodiments, but the implementation of the present invention is not limited thereto.
[0032] Example 1
[0033] A method for preparing a high-performance FeSiAl magnetic powder core includes the following preparation steps:
[0034] (1) The composition system is Fe 76 Si 14 Iron-based amorphous material of B7Nb2Cu1 (atomic percentage) was pulverized by gas atomization to obtain iron-based amorphous soft magnetic powder with an average particle size of 5μm.
[0035] (2) According to the mass ratio, mix 6 parts of the iron-based amorphous soft magnetic powder from step (1) with 100 parts of Fe with an average particle size of 20 μm. 85 Si9Al6 soft magnetic powder, 3 parts of pure Al powder with an average particle size of 3μm, 0.5 parts of aluminate coupling agent DL-411, 0.5 parts of zinc stearate lubricant and 6 parts of epoxy resin binder (solid content of 30%, diluent is ethyl acetate) are mixed evenly to obtain a mixed slurry.
[0036] (3) The mixed slurry obtained in step (2) is first hot-pressed and cured for 4 hours under the conditions of 80°C, 200MPa pressure and vacuum. Then, it is hot-pressed and annealed for 40 minutes under the conditions of 850°C, 600MPa pressure and mixed atmosphere containing O2 (10vt%) / Ar2 to obtain a high-performance FeSiAl magnetic powder core.
[0037] The magnetic powder core obtained in this embodiment has a compressive strength of 125.3 MPa (GB / T 6525-2019), a permeability (1MHz / 30mT) of 226.5, and a high-frequency loss (1MHz / 30mT) of 423 kW / m.3 .
[0038] Comparative Example 1
[0039] Compared with Example 1, this comparative example does not include iron-based amorphous soft magnetic powder in step (2), but the rest is the same.
[0040] The magnetic powder core obtained in this comparative example was tested and found to have a compressive strength of 158.5 MPa, a permeability (1MHz / 30mT) of 98.0, and a high-frequency loss (1MHz / 30mT) of 1374 kW / m. 3 .
[0041] The comparison results between Comparative Example 1 and Example 1 show that the present invention uses amorphous nanocrystalline soft magnetic powder to composite modify FeSiAl soft magnetic powder, which can significantly improve the high-frequency magnetic properties of the magnetic powder core.
[0042] Example 2
[0043] A method for preparing a high-performance FeSiAl magnetic powder core, compared with Example 1, the content of iron-based amorphous soft magnetic powder in step (2) is adjusted to 0.5 parts, and the rest are the same.
[0044] The magnetic powder core obtained in this embodiment has a compressive strength of 156.2 MPa, a permeability (1MHz / 30mT) of 114.7, and a high-frequency loss (1MHz / 30mT) of 815 kW / m. 3 .
[0045] Example 3
[0046] A method for preparing a high-performance FeSiAl magnetic powder core, compared with Example 1, the content of iron-based amorphous soft magnetic powder in step (2) is adjusted to 2 parts, and the rest are the same.
[0047] The magnetic powder core obtained in this embodiment has a compressive strength of 142.5 MPa, a permeability (1MHz / 30mT) of 139.2, and a high-frequency loss (1MHz / 30mT) of 727 kW / m. 3 .
[0048] Example 4
[0049] A method for preparing a high-performance FeSiAl magnetic powder core, compared with Example 1, the content of iron-based amorphous soft magnetic powder in step (2) is adjusted to 4 parts, and the rest are the same.
[0050] The magnetic powder core obtained in this embodiment has a compressive strength of 131.8 MPa, a permeability (1MHz / 30mT) of 174.3, and a high-frequency loss (1MHz / 30mT) of 586 kW / m. 3 .
[0051] Example 5
[0052] A method for preparing a high-performance FeSiAl magnetic powder core, compared with Example 1, the content of iron-based amorphous soft magnetic powder in step (2) is adjusted to 8 parts, and the rest are the same.
[0053] The magnetic powder core obtained in this embodiment has a compressive strength of 116.5 MPa, a permeability (1MHz / 30mT) of 295.1, and a high-frequency loss (1MHz / 30mT) of 457 kW / m. 3 .
[0054] Example 6
[0055] A method for preparing a high-performance FeSiAl magnetic powder core, compared with Example 1, the content of iron-based amorphous soft magnetic powder in step (2) is adjusted to 10 parts, and the rest are the same.
[0056] The magnetic powder core obtained in this embodiment has a compressive strength of 102.8 MPa, a permeability (1MHz / 30mT) of 355.9, and a high-frequency loss (1MHz / 30mT) of 506 kW / m. 3 .
[0057] The results from Examples 1 to 6 show that as the content of iron-based amorphous soft magnetic powder increases, the strength of the resulting magnetic powder core decreases, the permeability increases, and the high-frequency loss first decreases and then increases.
[0058] Comparative Example 2
[0059] Compared with Example 1, this comparative example does not add pure Al powder in step (2), but the rest is the same.
[0060] The magnetic powder core obtained in this comparative example was tested and found to have a compressive strength of 42.7 MPa, a permeability (1 MHz / 30 mT) of 70.4, and a high-frequency loss (1 MHz / 30 mT) of 1620 kW / m. 3 .
[0061] The comparison between Comparative Example 2 and Example 1 shows that the present invention uses low-melting-point pure Al powder as the binder phase and its in-situ oxide as the insulating coating phase, which can significantly improve the bonding force between soft magnetic powders and the insulating coating effect, thereby improving the strength of the magnetic powder core and the high-frequency magnetic properties.
[0062] Example 7
[0063] A method for preparing a high-performance FeSiAl magnetic powder core, compared with Example 1, the content of pure Al powder in step (2) is adjusted to 0.5 parts, and the rest are the same.
[0064] The magnetic powder core obtained in this embodiment has a compressive strength of 92.5 MPa, a permeability (1MHz / 30mT) of 156.4, and a high-frequency loss (1MHz / 30mT) of 688 kW / m. 3 .
[0065] Example 8
[0066] A method for preparing a high-performance FeSiAl magnetic powder core, compared with Example 1, the content of pure Al powder in step (2) is adjusted to 2 parts, and the rest are the same.
[0067] The magnetic powder core obtained in this embodiment has a compressive strength of 110.6 MPa, a permeability (1MHz / 30mT) of 187.1, and a high-frequency loss (1MHz / 30mT) of 536 kW / m. 3 .
[0068] Example 9
[0069] A method for preparing a high-performance FeSiAl magnetic powder core, compared with Example 1, the content of pure Al powder in step (2) is adjusted to 5 parts, and the rest are the same.
[0070] The magnetic powder core obtained in this embodiment has a compressive strength of 127.0 MPa, a permeability (1MHz / 30mT) of 225.2, and a high-frequency loss (1MHz / 30mT) of 408 kW / m. 3 .
[0071] Example 10
[0072] A method for preparing a high-performance FeSiAl magnetic powder core includes the following preparation steps:
[0073] (1) The composition system is Fe 80 Si 12 Iron-based amorphous material of B7Cu1 (atomic percentage) was pulverized by gas atomization to obtain iron-based amorphous soft magnetic powder with an average particle size of 2μm.
[0074] (2) According to the mass ratio, 5 parts of the iron-based amorphous soft magnetic powder from step (1) and 110 parts of Fe with an average particle size of 10 μm are mixed. 85 Si9Al6 soft magnetic powder, 3 parts of pure Al powder with an average particle size of 3μm, 0.5 parts of aluminate coupling agent DL-411, 0.5 parts of zinc stearate lubricant and 6 parts of epoxy resin binder (solid content of 30%, diluent is ethyl acetate) are mixed evenly to obtain a mixed slurry.
[0075] (3) The mixed slurry obtained in step (2) is first hot-pressed and cured for 5 hours under the conditions of 70°C, 250MPa pressure and vacuum. Then, it is hot-pressed and annealed for 50 minutes under the conditions of 750°C, 600MPa pressure and mixed atmosphere containing O2 (10vt%) / Ar2 to obtain a high-performance FeSiAl magnetic powder core.
[0076] The magnetic powder core obtained in this embodiment has a compressive strength of 130.5 MPa, a permeability (1MHz / 30mT) of 192.6, and a high-frequency loss (1MHz / 30mT) of 510 kW / m. 3 .
[0077] Example 11
[0078] A method for preparing a high-performance FeSiAl magnetic powder core includes the following preparation steps:
[0079] (1) The composition system is Fe 84 Si5B 10 Iron-based amorphous materials with Nb1 (atomic percentage) were atomized to produce iron-based amorphous soft magnetic powder with an average particle size of 10 μm.
[0080] (2) According to the mass ratio, 7 parts of the iron-based amorphous soft magnetic powder from step (1) and 120 parts of Fe with an average particle size of 30 μm are mixed. 85 Si9Al6 soft magnetic powder, 4 parts of pure Al powder with an average particle size of 3μm, 0.5 parts of aluminate coupling agent DL-411, 0.5 parts of zinc stearate lubricant and 8 parts of epoxy resin binder (solid content of 30%, diluent is ethyl acetate) are mixed evenly to obtain a mixed slurry.
[0081] (3) The mixed slurry obtained in step (2) is first hot-pressed for 3 hours under the conditions of 90℃ temperature, 150MPa pressure and vacuum, and then hot-pressed annealing and sintering treatment for 20 minutes under the conditions of 900℃ temperature, 600MPa pressure and mixed atmosphere containing O2 (5vt%) / Ar2 to obtain high-performance FeSiAl magnetic powder core.
[0082] The magnetic powder core obtained in this embodiment has a compressive strength of 113.8 MPa, a permeability (1MHz / 30mT) of 251.2, and a high-frequency loss (1MHz / 30mT) of 659 kW / m. 3 .
[0083] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for preparing a high-performance FeSiAl magnetic powder core, characterized in that: The preparation steps include the following: (1) Iron-based amorphous material with composition system Fe(100-xyz)SixByMz is pulverized by gas atomization to obtain iron-based amorphous soft magnetic powder; wherein 3≤x≤20, 2≤y≤15, 1≤z≤5, and M is at least one metal element among Cu, Nb, V, Ti, and Cr. (2) Iron-based amorphous soft magnetic powder is mixed evenly with FeSiAl soft magnetic powder, pure Al powder, aluminate coupling agent, lubricant and organic binder to obtain a mixed slurry. The organic binder has a solid content of 20-40% by mass and the diluent is ethyl acetate, cyclohexanone, propylene glycol methyl ether acetate, toluene or xylene thermosetting epoxy resin, acrylic resin or organosilicon resin. (3) The obtained mixed slurry is first hot-pressed and cured under vacuum conditions at a temperature of 60~100℃, and then hot-pressed and annealed under oxygen-containing atmosphere conditions at a temperature of 750~1000℃ to obtain a high-performance FeSiAl magnetic powder core. The average particle size of the iron-based amorphous soft magnetic powder in step (1) is 0.2~10μm; the average particle size of the FeSiAl soft magnetic powder in step (2) is 5~50μm; The mass fraction of each material in step (2) is as follows: 0.5-10 parts of iron-based amorphous soft magnetic powder, 100-120 parts of FeSiAl soft magnetic powder, 0.5-5 parts of pure Al powder, 0.2-1 parts of aluminate coupling agent, 0.2-1 parts of lubricant, and 1-10 parts of organic binder.
2. The method for preparing a high-performance FeSiAl magnetic powder core according to claim 1, characterized in that: The average particle size of the pure Al powder in step (2) is 0.2~5μm.
3. The method for preparing a high-performance FeSiAl magnetic powder core according to claim 1, characterized in that: The lubricant mentioned in step (2) is zinc stearate, magnesium stearate or polyvinyl ether.
4. The method for preparing a high-performance FeSiAl magnetic powder core according to claim 1, characterized in that: The pressure for hot pressing and curing in step (3) is 100~300MPa, and the time is 2~6h.
5. The method for preparing a high-performance FeSiAl magnetic powder core according to claim 1, characterized in that: The oxygen-containing atmosphere mentioned in step (3) is a mixture of oxygen and argon; the pressure of the hot pressing annealing sintering treatment is 500~800MPa and the time is 10~90min.
6. A high-performance FeSiAl magnetic powder core, characterized in that: It is prepared by the method described in any one of claims 1 to 5.
7. The application of the high-performance FeSiAl magnetic powder core as described in claim 6 in the fields of AI computing chips, servers, or communication equipment.
Citation Information
Patent Citations
Preparation method of metal powder injection molding sintered rare earth magnet
CN117133538A
Amorphous nanocrystalline soft magnetic material with high saturation flux density and preparation method of amorphous nanocrystalline soft magnetic material
CN119361280A
Soft magnetic composite material coated with nano metal oxide insulating material and preparation method of soft magnetic composite material
CN119517596A
